How to be a brilliant mentor : developing outstanding teachers - Wright, Trevor Ed (Routledge, 2018)
How to be a Brilliant Mentor is an informal and accessible guide that provides ideas and reassurance to help support you in your work as a teacher training mentor. Written by experienced trainers, teachers and mentors, it brings together a wealth of expertise and research, offering clear and practical guidelines to enhance your mentoring, helping you to analyse your own practice and understand the complex and often ambiguous role of the mentor in school.